(untitled) (Biological Sciences - PJSIR, 1997)
The phosphate rock occurrences at Hazara inPakistan are apart of Cambrian-Jurassic sequence which hosts rock phos- phate associated with dolomite and chert. The geology of the phosphate bearing district of Hazara which is situated in Northern Pakistan has drawn attention of leading geologists of the subcontinent for over a century. Important contributions to the geology of Hazara were made by Middlemiss [I] and Wadia [2]. After the independence of Pakistan, extensive studies on geology of the area were made by Marks and Ali [3] and Calkins and Matin [4]. The Abbot- tabad district of Hazara assumed further importance when phosphate was discovered by Latif [5,6]. A number of studies on Hazara phosphorite deposits were made by British Mining Consultants and Sarhad Development Authority [7-13].